Critical role of lysosomes in the dysfunction of human Cardiac Stem Cells obtained from failing hearts. (1st August 2016) - Gianfranceschi, Giuseppe; Caragnano, Angela; Piazza, Silvano; Manini, Ivana; Ciani, Yari; Verardo, Roberto; Toffoletto, Barbara; Finato, Nicoletta; Livi, Ugolino; Beltrami, Carlo Alberto; Scoles, Giacinto; Sinagra, Gianfranco; et al.
Abstract: The in vivo reparative potential of Cardiac Stem Cells (CSC), cultured from explanted failing hearts (E-), is impaired by cellular senescence. Moreover, E-CSC are characterized, with respect to CSC obtained from healthy donors (D-), by an arrest in the autophagic degradation. Although the lysosome plays a pivotal role in cellular homeostasis and defects of this organelle may be associated with aging and heart failure, the lysosomal function of CSC has never been investigated. The aim of this work was to focus on the Lysosomal Compartment (LC) of E-CSC, evaluating elements that could jeopardize lysosome functionality. Methods and results: Bioinformatics analysis conducted on genes differentially expressed between D- and E-CSC identified lysosomal-related gene sets as significantly enriched. Moreover, 29 differentially expressed genes were part of CLEAR (Coordinated Lysosomal Expression and Regulation) gene network, by which Transcription Factor EB (TFEB) regulates cellular clearance. Consistently, live cell imaging and flow cytometry analyses showed that the lysosomes of E-CSC are less acidic than the D-CSC ones. Furthermore, confocal microscopy showed in E-CSC: an accumulation of intralysosomal lipofuscins, a reduction of cathepsin B activity, evidence of lysosome membrane permeabilization, and the reduction of the nuclear active TFEB. The use of Rapamycin (TORC1 inhibitor) was able on one hand to increase TFEB activation and, on the other hand, to reduce lipofuscin mass, potentiating the lysosomal functionality. Conclusions: This study demonstrated for the first time that E-CSC are characterized by a blunted activation of TFEB and an altered proteostasis. TORC1 hyperactivation plays a central role in this phenomenon. Graphical abstract: